2021
DOI: 10.1186/s12891-020-03928-5
|View full text |Cite
|
Sign up to set email alerts
|

Total spine magnetic resonance imaging for detection of multifocal infection in pyogenic spondylodiscitis: a retrospective observational study

Abstract: Background Due to the unspecific symptoms of spondylodiscitis (SpD), an early radiological examination is necessary. However, controversially discussed is the need for magnetic resonance imaging of the entire spine to exclude multisegmental infections and to determine the required surgical interventions. The aims of this study were to assess the incidence of multilevel non-contiguous pyogenic SpD and compare comorbidities, pain symptoms, and subsequent surgical strategies between unifocal (uSpD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…It is worth mentioning that 17% of patients had multifocal infections at the time of diagnosis. Henkelmann et al, 30 in a retrospective series of 69 patients, found a prevalence of multifocal spondylodiscitis of 13%. Similar prevalence was observed by Stangenberg in 211 patients.…”
Section: Discussionmentioning
confidence: 95%
“…It is worth mentioning that 17% of patients had multifocal infections at the time of diagnosis. Henkelmann et al, 30 in a retrospective series of 69 patients, found a prevalence of multifocal spondylodiscitis of 13%. Similar prevalence was observed by Stangenberg in 211 patients.…”
Section: Discussionmentioning
confidence: 95%
“…A retrospective study of multifocal spondylodiscitis identified two patients with rheumatoid arthritis who were under anti-TNF-alpha drugs (namely adalimumab and etanercept). 6,7 Pyogenic spondylodiscitis most frequently affects the lumbar spine followed by thoracic and cervical, with multifocal involvement occurring only in 4-8% of cases 2,4,8 . Cervical involvement is found to be associated with the presence of epidural abscess more frequently as well as neurological deficits when compared with the other segments of the spine.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the values previously reported in the literature for rates of multifocal involvement in spinal infection. 30 , 31 However, no direct relationship has been found between multifocal involvement and severity of spinal infection in the literature. 31 …”
Section: Discussionmentioning
confidence: 99%
“… 30 , 31 However, no direct relationship has been found between multifocal involvement and severity of spinal infection in the literature. 31 …”
Section: Discussionmentioning
confidence: 99%